Psychological stress among football coaches - قلول , محمد (Journal of Sport Science Technology and Physical Activities, 2025)
The Object of the study aims to identify the most important psychological pressures faced by football coaches and for this purpose, we used the descriptive approach by following the survey method on a sample composed of 60 football coaches who were selected randomly. and for data collection, we used a tool of retrospective survey tool, the personal interview and the psychological stress scale for football coaches by Muhammad Hassan Allawi. After collecting the results and having treated them statistically, we conclude that the most important factors that increase the psychological pressure of the football coach are those related to the senior management of the team, as well as the players and their relationship with the coach, the factors of lack of encouragement from the public, the weakness of the coach’s personality and the negative criticism methods of the media. On this basis, the study recommended allocating training courses for coaches to face such pressures and directing senior administrations on the importance of the coach in forming a cohesive team and resorting to constructive criticism by the media and its box. If the soccer coach does not receive support from the administration, the media and the players And the audience, this will inevitably affect the results of the team as a whole.